From Questions to Proofs. Between the Logic of Questions and Proof Theory - Leszczyńska-Jasion, Dorota (Wydawnictwo Naukowe Wydziału Nauk Społecznych UAM, 2018)
This work tackles issues lying at the intersection of question theory and reason-ing theory, leading from the issue of questions to proof-theoretical matters in broadly understood erotetic logic. Dorota Leszczyńska-Jasion consciously posi-tions her deliberations within the IEL (Inferential Erotetic Logic) paradigm, placing particular emphasis on so-called Socratic proofs. The book […] is consistent with the tradition of the logic community from which it derives, meaning the tradition of research into erotetic logic pioneered and developed in Poznań by Professor Andrzej Wiśniewski. […] At the same time, the book enriches the said tradition with ideas and solutions that have emerged over many years in the author’s own, independent investigations. This work can be expected to worthily represent the Polish logic community internationally, as an important and original contribution to the logic theory of questions and proofs.
Keywords: logic of questions; Inferential Erotetic Logic; proof theory